(untitled) (New York, 2016)
Building Citizenship: Civics & Economics engages students in principles that serve as the foundation of our government and economy while emphasizing real-life citizenship and personal financial literacy. This practical, interactive Civics and Economics curriculum includes a strong emphasis on critical thinking, project-based learning, document-based analysis and questions, and the development of close reading skills. Connect to core civics and economics content with an accessible, student-friendly text aligned to the Understanding by Design® instructional approach
Keywords: Công dân,Civics